Economic benefits of climate-smart agricultural practices to smallholder farmers in the Indo-Gangetic Plains of India - Khatri-Chhetri, Arun; Aryal, Jeetendra Prakash; Sapkota, Tek Bahadur; Khurana, Ritika (Current Science Association, 2016)
Small landholders can implement a range of climatesmart agricultural (CSA) practices and technologies, in order to minimize the adverse effects of climate change and variability, but their adoption largely depends on economic benefits associated with the practices. To demonstrate the potential economic benefits of CSA practices, we conducted a study with smallholder farmers in the Indo-Gangetic Plains (IGP) of India. Among the CSA practices and technologies including use of improved crop varieties, laser land levelling, zero tillage, residue management, site specific nutrient management, and crop diversification, a majority of the farmers prefer to use improved crop varieties, crop diversification, laser land levelling and zero tillage practice. We estimated the cost of adoption, change in yields and income for the implementation of three major CSA practices in rice- wheat system. The average cost of adoption were +1,402, +3,037 and -1,577 INR ha-1 for the use of improved crop varieties, laser land levelling and zero tillage respectively. Results show that farmers can increase net return of INR 15,712 ha-1 yr-1 with improved crop varieties, INR 8,119 ha-1 yr-1 with laser levelling and INR 6,951 ha-1 yr-1 with zero tillage in rice-wheat system. Results also show that the combination of improved seeds with zero tillage and laser land levelling technologies can further improve crop yields as well as net returns. The econometric analysis indicates that implementations of CSA practices and technologies in smallholder farms in the IGP of India, have significant impacts on change in total production costs and yield in rice-wheat system.